Maximizing frequency security margin via conventional generation dispatch and battery energy injection - Zhao, Xiaohui; Wei, Hua; Qi, Junjian; Li, Peijie; Bai, Xiaoqing (Frontiers in Energy Research, 2023)
To quantitatively evaluate the frequency stability margin during primary frequency control period following an under-frequency event, this paper presents a dynamic frequency response constrained optimal power flow (OPF) model. In this model, frequency security margin is defined and maximized by adjusting pre-disturbance generation outputs of conventional units and injections of battery energy storage system (BESS) immediately after a disturbance. Two nonlinear characteristics in speed-governing systems are considered and described as smooth and differentiable formulations to facilitate their incorporations into the proposed optimization model. A graphical tool is also provided to enable region-wise frequency security assessment based on the obtained maximum frequency security margin. Simulation results on WSCC 3-machine 9-bus system and New England 10-machine 39-bus system validate the suggested margin metric and the effectiveness of the proposed method.